Hubungan Kerapatan Tanah, Karbon Organik Tanah dan Cadangan Karbon Organik Tanah Di Kawasan Agroforestri Tembawang Nanga Pemubuh Sekadau Hulu Kalimantan Barat - Riza Linda, Tirta Sari, Rafdinal (Jurnal Protobiont, 2017)
Soil Organic carbon is an organic matter contained in or on the soil surface which derives from natural carbon compounds. Soil becomes an important representation of organic carbon stock in long-term period of land ecosystem, because soil accumulates carbon larger than those in plant biomass and atmosphere. This research aims to study the correlation between soil density, soil organic carbon, and soil organic carbon stock in tembawang agroforestry area Nanga Pemubuh Sekadau Hulu West Kalimantan. The results show that soil density has a negative correlation and a real effect on soil organic carbon, and it has positive correlation and a real effect on soil organic carbon stock.